Naval Academy Cadets Voyage Introduces National Culture - Mirza Mirza; Hikmah Zakky Almubaroq (Faculty of Social Science, Universitas Negeri Padang, 2022)
As the largest archipelagic country in the world with a strategic position and with having alarge wealth of natural resources, Indonesia constitutes a country that has tremendous allure to other countries that have an interest. In order to manage abundant natural resources, of course it must be supported by good Indonesian human resources. This is in line with the policy of the President of the Republic of Indonesia H. Joko Widodo,that the development of human resources constitutes top priority in his government policy for 2019-2024. This priority also in the navy which has motto Jalesveva Jayamahe (in the sea that we are victorious). In order to generate qualified Indonesian human resources in order to build and maintain the sovereignty of the unitary state of the Republic of Indonesia and to implement government policies and Kasal policies, especially in generating officers, of course it can be realized and determined fundamentally by the educational institution system. Therefore, it is necessary to revise these regulations so that later they will be better and can accommodate changes that occur and eliminate existing problems. The purpose of this study is to provide policy authors with tools to understand and predict service behavior as operational and policy requirements change so that the new regulations will be better.